Analysis of Lamina Papyracea Area and Ethmoid Sinus Volume in Indonesian Patients Undergoing Paranasal Sinus CT Scan - Wahyuni, Wahyuni; Idris, Nurlaily; Muis, Mirna; Zainuddin, Andi Alfian; Perkasa, Muhammad Fadjar; Ilyas, Muhammad (Fakultas Kedokteran Universitas Brawijaya, 2020)
Of the rhinosinusitis (CRS) patients, half of whom require surgical intervention. Functional endoscopic sinus surgery (FESS) is a standard treatment of CRS and sinonasal polyposis. Orbito-ocular complications can occur during FESS. The lamina papyracea (LP) is the weakest point of the medial wall of the orbit. The variability in the size and shape of the paranasal sinuses is important in the FESS procedure. The ethmoid sinus is the most complex paranasal sinuses. Preoperative evaluation using computed tomography (CT) is mandatory for all patients undergoing FESS. This study aimed to determine the lamina papyracea area and ethmoid sinuses volume in patients who underwent a CT scan of paranasal sinuses. This study was a descriptive study on 103 patients who underwent a CT scan of paranasal sinuses in the Radiology Department of Hasanuddin University General Hospital, Makassar, from January to August 2019. The lamina papyracea area and ethmoid sinus volume were measured based on age and gender. The results showed that the average of lamina papyracea size and ethmoid sinus volume was greater in males than in females. There was a correlation between age and posterior height of left lamina papyracea (p=0.02), but no correlation between ethmoid sinuses volume and age.